1991
DOI: 10.1038/bjc.1991.242
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of isolated liver perfusion with mitomycin C in the treatment of liver tumours of rat colorectal cancer

Abstract: Summary Dose limiting systemic toxicity prevents sufficient exploitation of the steep dose response relationship of most anticancer agents. In our rat liver tumour model (the CC531 colorectal carcinoma), isolated liver perfusion allows administration of higher doses of mitomycin C than hepatic artery infusion, while systemic toxicity remains minimal. To determine the temporal pattern of mitomycin C induced cytokinetic changes, we analysed flow cytometric DNA histograms of CC53 1 liver tumours from rats treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…However, MMC is an excellent candidate for regional administration because of the high first pass hepatic extraction that assures high local drug concentrations with a reduced systemic toxicity [18,19]. In a rat model of liver metastases from colorectal cancer, isolated liver perfusion with MMC induced a marked DNA synthesis inhibition and even complete tumour remission [20]. MMC has been used intra-arterially as regional chemotherapy for metastatic colorectal cancer and has given good responses [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, MMC is an excellent candidate for regional administration because of the high first pass hepatic extraction that assures high local drug concentrations with a reduced systemic toxicity [18,19]. In a rat model of liver metastases from colorectal cancer, isolated liver perfusion with MMC induced a marked DNA synthesis inhibition and even complete tumour remission [20]. MMC has been used intra-arterially as regional chemotherapy for metastatic colorectal cancer and has given good responses [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Re-absorption of the 1979; Millar et al, 1986;Bates & Mackillop, 1990) ILP with mitomycin C also resulted in complete remissions in rats (Marinelli et al, 1991). The technique of isolated liver perfusion has been already extensively and successfully tested in patients by different groups (Aigner et al, 1988;Hafstr6m et al, 1990) without serious (post-) operative complications.…”
Section: Effect Ofmelphalan On Tumour Growthmentioning
confidence: 98%
“…Although ILP with 5-fluorouracil (FUra) and mitomycin C (MMC) has recently been applied in patients by Aigner et al (1988), data on the effectiveness of this approach are not yet available. In experimental studies in rats, the effectiveness of ILP has been reported for FUra (Radnell et al, 1990;Marinelli et al, 1990b) and MMC (Marinelli et al, 1991). Only with MMC complete remissions and a significantly prolonged survival has been reported (Marinelli et al, 1991).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Chemotherapy using fluoropyrimidines, often in combination with modulators like leucovorin, methotrexate or interferon, is most often used in these patients, but with a minimal increase in survival rates (Meropol et al, 1995). Hepatic arterial infusion of chemotherapeutics results in higher response rates and survival in preclinical and clinical studies (Marinelli et al, 1991;Kemeny, 1995), indicating that local drug application may offer good prospects.…”
mentioning
confidence: 99%